Implementing Project-Based Learning Focusing on Business Presentations to Promote the Speaking Ability of Rajamangala University of Technology Isan Students - Nuamkoksoong, Kamontip; Lornklang, Thanachart (Ratchaphruek Journal, 2026)
This research aimed to 1) examine the effects of learning English through project-based learning, focusing on business presentations on the English-speaking ability of Rajamangala University of Technology Isan students, and 2) study students' satisfaction with learning English through PBL, focusing on business presentations. The samples involved 44 first-year students from Rajamangala University of Technology Isan who were selected by using cluster random sampling. The instruments used in the study were a lesson plan incorporating PBL with a focus on business presentations, an English-speaking ability test, and a questionnaire. Analysis of data used means ( ), standard deviation (S.D.), and a dependent t-test. The results revealed that the post-test mean score of students’ English-speaking ability was significantly higher than the pre-test at the .05 level of significance. In addition, the satisfaction questionnaire indicated that students were highly satisfied with learning English through the PBL approach with business presentation content. The findings confirm that project-based learning using business presentations can effectively enhance students’ English-speaking ability.